El maíz forrajero como suplemento alimenticio en el ganado bovino para el incremento de la producción lechera” - Arana Bustamante, Walter Wilfrido (2020)
At certain times of the year, small and medium-sized producers have difficulties feeding their livestock; drought seasons have a direct impact on the performance of the animal and on the producer's economy. The objective of the present work was to know the effect exerted by corn forage supplementation on bovine milk production. This review brings together bibliographic information that allows us to recognize that different types of forage crops can be implemented in animal nutrition that provide sufficient amounts of energy to meet the needs of animals to maintain their body reserves; so looking for alternatives to feed them will always be a great challenge that they will have to face. At present the use of forage corn is one of the best alternatives that the producer has, since this crop adapts very well to different climatic and soil conditions, it also has a high volume of forage with excellent nutritional characteristics when compared to other forage crops; It has a total of digestible nutrients (TND) equal to or greater than 70% on a dry basis, with its crude fiber content equal to or greater than 18%. Through this document, it has been possible to assess the benefits that can be obtained not only in the maintenance of dairy cattle, but also in productive gains, for which many institutions seeking favorable productive results have implemented it in food diets in times of scarcity, managing to improve on many occasions the health of the animal and its milk production. Thanks to this research, records were found in which corn forage (FM) was provided as a food supplement in times of scarcity, and others as a supplement to their diets, seeking favorable results, but the most important thing is that it was known through studies To supplement with FM, there were no large increases in production, however, it would help to keep livestock active and healthy until these moments of scarcity were overcome.